The therapeutic potential of antioxidants, ER chaperones, NO and H2S donors, and statins for treatment of preeclampsia - Cindrova-Davies, Tereza (Frontiers in Pharmacology, 2014)
Preeclampsia is a complex multifactorial disease. Placental oxidative stress, a result of deficient spiral artery remodeling, plays an important role in the pathophysiology of preeclampsia. Antiangiogenic factors secreted from malperfused placenta are instrumental in mediating maternal endothelial dysfunction and consequent symptoms of preeclampsia; the mechanism is likely to involve increased ET-1 secretion and reduced NO bioavailability. Therapeutic interventions so far remain only experimental and there is no established remedy for the treatment of preeclampsia. This review concentrates on the evidence for the therapeutic potential of antioxidants, ER chaperones, NO and H2S donors, and statins. These compounds display pleitropic antioxidant, anti-inflammatory, and pro-angiogenic effects in animal and in vitro studies. Although clinical trials on the use of antioxidant vitamins in pregnancy proved largely unsuccessful, the scope for their use still exists given the beneficial cardioprotective effects of antioxidant-rich Mediterranean diet, periconceptual vitamin use and the synergistic effect of vitamin C and l-arginine. Encouraging clinical evidence exists for the use of NO donors, and a clinical trial is underway testing the effect of statins in treatment of preeclampsia. H2S recently emerged as a novel therapeutic agent for cardiovascular disease, and its beneficial effects were also tested in animal models of preeclampsia. It is risky to prescribe any medication to pregnant women on a large scale, and any future therapeutic intervention has to be well tested and safe. Many of the compounds discussed could be potential candidates.